Standards for Storytelling-Based Nursing Communication to Reduce Hospitalization Anxiety in Preschool Children: A Systematic Review - Suraya, Citra; Wisuda, Aris Citra; Sansuwito, Tukimin bin; Dioso, Regidor III; Rusmarita (Yayasan Rumah Ilmu Professor, 2025)
Hospitalization often triggers significant anxiety in preschool children due to their developmental vulnerability, separation from caregivers, and exposure to unfamiliar medical environments. If left unaddressed, this anxiety can result in both short- and long-term psychological and behavioral issues. Storytelling-based nursing communication has emerged as a promising intervention to help children understand and cope with hospitalization; however, standardized approaches remain limited. This study aims to identify and synthesize existing evidence on the standards of storytelling-based nursing communication for reducing hospitalization-related anxiety in preschool children. Using a descriptive analytical approach, a systematic search was conducted across PubMed, Scopus, ScienceDirect, and CINAHL for peer-reviewed studies published between 2020 and 2025. Eligible studies included nurse-led storytelling interventions targeting hospitalized preschoolers. Both qualitative and quantitative research was reviewed and critically appraised. The review identified fourteen relevant studies. Storytelling interventions were consistently effective in reducing anxiety, particularly when implemented using standardized methods such as structured narratives, visual aids (e.g., puppets, books, digital media), therapeutic play, and nurse communication training. These approaches enhanced emotional expression, improved nurse-child interaction, and fostered more positive hospital experiences. In conclusion, standardized storytelling-based nursing communication is an effective strategy for alleviating anxiety in hospitalized preschool children. Its broader implementation in pediatric nursing practice requires further research, training, and policy development.